Designing Hybrid Learning Tools Based on Lesson Study for Learning Community against Metacognition Ability - Madinda, Diah Putri; Hobri, Hobri; Hadi, Alfian Futuhul; Fauziyah, Mailulah Ely (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
This study aims to analyse the outcomes of establishing valid, practical, effective Hybrid Learning tools based on Lesson Study for Learning Community (LSLC) and their impact on students' metacognitive abilities. Research and Development (R D) and experimental research are used to conduct the study. The research subjects are consisted of three classes of 7th grade students. Collaborative Learning and Learning Community are implemented which are the components of LSLC. The 4-D model, which includes define, design, develop, and disseminate, is used to develop learning tools. Lesson plans, worksheets, and a metacognition ability test were created as a result of the research and met the criteria of being of valid, practical, and effective. Based on experimental research, there is a significant effect of Hybrid Learning tools based on Lesson Study for Learning Community on students' metacognitive abilities with p-value of 0.001 (sig 0.05).Penelitian ini bertujuan untuk menganalisis hasil pengembangan perangkat pembelajaran Hybrid Learning berbasis Lesson Study for Learning Community yang valid, praktis, efektif dan menganlisis pengaruhnya terhadap kemampuan metakognisi siswa. Metode penelitian yang digunakan dalam penelitian ini yaitu metode penelitian kombinasi atau mix method. Penelitian ini menggabungkan dua bentuk penelitian yaitu penelitian pengembangan (research and development) dan penelitian eksperimen. Subjek penelitian dalam penelitian ini terdiri dari tiga kelas siswa VII yang terdiri dari kelas uji coba, kelas eksperimen dan kelas kontrol. Komponen Lesson Study for Learning Community yang diterapkan yaitu Collaborative Learning dan Learning Community. Proses pengembangan perangkat pembelajaran dilaksanakan melalui 4-D yaitu pendefinisian, perancangan, pengembangan dan penyebaran. Hasil pengembangan perangkat pembelajaran Hybrid Learning berbasis Lesson Study for Learning Community berupa RPP, LKS dan tes kemampuan metakognisi siswa yang valid, praktis dan efektif. Berdasarkan penelitian eksperimen dan observasi, terdapat pengaruh yang signifikan perangkat pembelajaran Hybrid Learning berbasis Lesson Study for Learning Community terhadap kemampuan metakognisis siswa dengan nilai signifikasi 0.001 .